Recensions (Apocrypha, 2023)
Abstract Baumgarten, Joseph M., Studies in Qumran Law and Thought, édité par Ruth A. Clements et Daniel R. Schwartz (Damien Labadie) Barc, Bernard, Du sens visible au sens caché de l’Écriture, Arpenteurs du temps, Essai sur l’histoire religieuse de la Judée à la période hellénistique, Nouvelle édition (Jean-Daniel Dubois) Lemelin, Isabelle, À l’origine des femmes martyres. La mère de 2 Maccabées 7 (Damien Labadie) Hakola, Raimo, Orpana, Jessi et Huotari, Paavo (éd.), Scriptures in the Making : Texts and Their Transmission in Late Second Temple Judaism (Claire Clivaz) Patmore, Hector M. et Lössl, Josef (éd.), Demons in Early Judaism and Christianity : Characters and Characteristics (Damien Labadie) Chapot, Frédéric (éd.), Les récits de la destruction de Jérusalem (70 ap. J.-C.). Contextes, représentations et enjeux, entre Antiquité et Moyen Âge (Anna Van den Kerchove) Pardee, Cambry G. et Tripp, Jeffrey M. (éd.), Sacred Texts & Sacred Figures : The Reception and Use of Inherited Traditions in Early Christian Literature. A Festschrift in Honor of Edmondo F. Lupieri (Joseph Verheyden) Vercruysse, Jean-Marc (éd.), Les tentations du Christ (Maïeul Rouquette) Eurell, John-Christian, Peter’s Legacy in Early Christianity. The Appropriation and Use of Peter’s Authority in the First Three Centuries (Céline Rohmer) Frey, J., den Dulk, M. et van der Watt, J. G. (éd.), 2 Peter and the Apocalypse of Peter : Towards a New Perspective, Radboud Prestige Lectures by Jörg Frey (Jean-Daniel Dubois) Pouderon, Bernard, Métamorphoses de Simon le Magicien, Des Actes des apôtres au Faustbuch, Wie ein lebendiges Gestirn/Comme un astre vivant (Jean-Paul Lesimple) The Protevangelium of James, introduced, edited & translated by J. K. Elliott. With a commentary by Patricia M. Rumsey (Paul-Hubert Poirier) Vuković, Marijana, Survival and Success of Apocryphal Childhood of Jesus : Reception of the Infancy Gospel of Thomas in the Middle Ages (Zbigniew Izydorczyk) Sevrin, Jean-Marie, Études sur l’Évangile selon Thomas et la littérature gnostique, recueil d’articles édité par Paul-Hubert Poirier et Joseph Verheyden (Jean-Daniel Dubois) Chiapparini, Giuliano, Clemente di Alessandria, Estratti da Teodoto, Frammenti delle perdute Ipotiposi (Jean-Daniel Dubois) Lehtipuu, Outi, et Petersen, Silke (éd.), Ancient Christian Apocrypha. Marginalized Texts in Early Christianity (Maïeul Rouquette) Nicklas, Tobias, Spittler, Janet E. et Bremmer, Jan N. (éd.), The Apostles Peter, Paul, John, Thomas and Philip with their Companions in Late Antiquity (Priscille Marschall) Acts of John, translated by Joey McCollum and Brent Niedergall with the assistance of Derek G. T. DeMars, Bobby Howell, and Stephen M. Young (Boris Paschke) Hilaire de Poitiers, Lettre sur les Synodes, texte critique, introduction et notes par Michael Durst, traduction par André Rocher (†) / Athanase d’Alexandrie, Tome aux Antiochiens. Lettres à Rufinien, à Jovien et aux Africains, introduction, traduction et notes par Annick Martin et Xavier Morales, texte grec par H. C. Bennecke, U. Heil, C. Müller, A. van Stockhausen et A. Wintjes (Anna Van den Kerchove) Lytvynenko, Viacheslav V. (éd.), Athanasius of Alexandria, Oratio III contra Arianos : Old Slavonic Version and English Translation (Susana Torres Prieto) Müller, Veronika, Julian von Aeclanum – Ad Florum liber primus. Text, Übersetzung und Kommentar (Giulio Malavasi) Zaganas, Dimitrios, L’Hexaemeron d’Anastase le Sinaïte. Son authenticité, ses sources et son exégèse allégorisante (Rémi Gounelle) Dixon, Carl, The Paulicians. Heresy, Persecution and Warfare on the Byzantine Frontier, c. 750-880 (Zaroui Pogossian) Calzolari, Valentina, The Apocryphal Acts of the Apostles in Armenian (Jacob A. Lollar) Gippert, Jost, Outtier, Bernard, Kim, Sergey, et al., Catalogue of the Georgian Manuscripts of the Holy Monastery of Iviron (Susana Torres Prieto) Cioată, Marie, Miltenova, Anissava et Timotin, Emanuela (éd.), Biblical Apocrypha in South-Eastern Europe and Related Areas : Proceedings of the Session Held at the 12th International Congress of South-East European Studies (Bucharest, 2-6 September 2019) (Zbigniew Izydorczyk) Leurini, Claudia, Hymns in Honour of the Hierarchy and Community, Installation Hymns and Hymns in Honour of Church Leaders and Patrons, Middle Persian and Parthian Hymns in the Berlin Turfan Collection (Jean-Daniel Dubois) Clark, Larry, Uygur Manichaean Texts. Texts, Translations, Commentary, vol. III : Ecclesiastical Texts (Jean-Daniel Dubois)